Fructans of the saline world - TOKSOY ÖNER, EBRU (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
Saline and hypersaline environments make up the largest ecosystem on earth and the organisms living in such water-restricted environments have developed unique ways to cope with high salinity. As such these organisms not only carry significant industrial potential in a world where freshwater supplies are rapidly diminishing, but they also shed light upon the origins and extremes of life. One largely overlooked and potentially important feature of many salt-loving organisms is their ability to produce fructans, fructose polymers widely found in various mesophilic Eubacteria and plants, with potential functions as storage carbohydrates, aiding stress tolerance, and acting as virulence factors or signaling molecules. Intriguingly, within the whole archaeal domain of life, Archaea possessing putative fructan biosynthetic enzymes were found to belong to the extremely halophilic class of Halobacteria only, indicating a strong, yet unexplored link between the fructan syndrome and salinity. In fact, this link may indeed lead to novel strategies in fighting the global salinization problem. Hence this review explores the unknown world of fructanogenic salt-loving organisms, where water scarcity is the main stress factor for life. Within this scope, prokaryotes and plants of the saline world are discussed in detail, with special emphasis on their salt adaptation mechanisms, the potential roles of fructans and fructosyltransferase enzymes in adaptation and survival as well as future aspects for all fructanogenic salt-loving domains of life.
Keywords: Salinity; Halophile; Halophyte; Fructan; Fructosyltransferase; Archaea; WHEAT TRITICUM-AESTIVUM; SALT-TOLERANCE; SOIL-SALINITY; GLYCINE-BETAINE; ABSCISIC-ACID; FREEZING TOLERANCE; CRYSTAL-STRUCTURE; IRRIGATION WATER; ENZYME-ACTIVITY; AMINO-ACID